Characteristics of Interstitial Fibrosis and Inflammatory Cell Infiltration in Right Ventricles of Systemic Sclerosis-Associated Pulmonary Arterial Hypertension. (3rd August 2010) - Overbeek, Maria J.; Mouchaers, Koen T. B.; Niessen, Hans M.; Hadi, Awal M.; Kupreishvili, Koba; Boonstra, Anco; Voskuyl, Alexandre E.; Belien, Jeroen A. M.; Smit, Egbert F.; Dijkmans, Ben C.; Vonk-Noordegraaf, Anton; Grünberg, Katrien
Abstract : Objective . Systemic sclerosis-associated pulmonary arterial hypertension (SScPAH) has a disturbed function of the right ventricle (RV) when compared to idiopathic PAH (IPAH). Systemic sclerosis may also affect the heart. We hypothesize that RV differences may occur at the level of interstitial inflammation and—fibrosis and compared inflammatory cell infiltrate and fibrosis between the RV of SScPAH, IPAH, and healthy controls. Methods . Paraffin-embedded tissue samples of RV and left ventricle (LV) from SScPAH (n = 5 ) and IPAH (n = 9 ) patients and controls (n = 4 ) were picrosirius red stained for detection of interstitial fibrosis, which was quantified semiautomatically. Neutrophilic granulocytes (MPO), macrophages (CD68), and lymphocytes (CD45) were immunohistochemically stained and only interstitial leukocytes were counted. Presence of epi- or endocardial inflammation, and of perivascular or intimal fibrosis of coronary arteries was assessed semiquantitatively (0–3: absent to extensive). Results . RV's of SScPAH showed significantly more inflammatory cells than of IPAH (cells/mm 2, mean ± s d MPO 11 ± 3 versus6 ± 1 ; CD68 11 ± 3 versus6 ± 1 ; CD45 11 ± 1 versus5 ± 1, P < .05 ) and than of controls. RV interstitial fibrosis was similar in SScPAH and IPAH (4 ± 1 versus5 ± 1 %, P = .9 ), and did not differ from controls (5 ± 1 %, P = .8 ). In 4 SScPAH and 5 IPAH RV's foci of replacement fibrosis were found. No differences were found on epi- or endocardial inflammation or on perivascular or intimal fibrosis of coronary arteries. Conclusion . SScPAH RVs display denser inflammatory infiltrates than IPAH, while they do not differ with respect to interstitial fibrosis. Whether increased inflammatory status is a contributor to altered RV function in SScPAH warrants further research.